Morphological and physiological consequences of a dietary restriction during early life in bats. (31st December 2019) - Meniri, Magali; Hebinger, Doriane; Sorlin, Mahaut; Ramirez, Marine; Kauffmann, Emilie; Vallat, Armelle J; Glauser, Gaëtan; Fasel, Nicolas; Helfenstein, Fabrice
Abstract: Early life adverse conditions can have major consequences on an individual's life history traits. Oxidative stress has been hypothesized to be one main mechanism underlying the negative consequences of early life adverse conditions. To test this hypothesis, we restricted the food availability of Seba's short-tailed bat ( Carollia perspicillata ) mothers of unweaned pups for 10 days, followed by ad libitum provisioning. We also had a control, unrestricted group. We explored the morphological consequences of dietary restriction during early life by measuring growth rate. We also measured four markers of blood oxidative balance during growth. We assessed the level of cortisol, and its inactive form cortisone, in the hair of the pups at the end of growth. Finally, we monitored survival during the first year. Food restriction triggered a slowdown in growth followed by catch-up growth when ad libitum feeding was restored which did not lead to full compensation in size or mass compared to control individuals. We found that higher growth rate was associated with elevated oxidative damage, suggesting an oxidative cost to growth. However, we found no clear evidence for physiological costs specific to the catch-up growth. Survival after a year was not impacted by the treatment, the oxidative balance or the level of glucocorticoids at the end of growth. In conclusion, our results show that individuals were able to efficiently mitigate the short-term consequences of adverse early life conditions. However, consequences might arise in the long-term, and could impact reproductive success or lifespan. Lay Summary: Early life adverse conditions can have life-long consequences, but the mechanisms underlying such changes remain poorly understood. Using an experimental approach, we monitored the morphological consequences of early life adversity on a long-lived mammal, the Seba's short-tailed bats. We explored whether physiological stress and oxidative stress could provide a mechanism explaining the expected consequences of a bad start. Interestingly, these fruit-eating bats were able to efficiently mitigate the short-term consequences of a bad start.